Los hábitos alimenticios y la lonchera saludable de los niños de inicial 2 paralelo “A” de la Unidad Educativa “Dr. Gabriel García Moreno” del cantón Guano, provincia de Chimborazo. - Tingo Sampedro, Dangela Mishel (2024)
This research addresses the eating habits and healthy lunch boxes in kindergarten children two parallel "A" of the Educational Unit "Dr. Gabriel García Moreno." The theme highlights the importance of eating habits and a healthy lunchbox since it is evident today that children are aggressively affected by not consuming nutritious food, having health and academic effects, among others, so it is essential to be aware of the importance of a balanced diet from an early age. Methodologically, it is primary research with a qualitative approach and a non-experimental design; due to its level and scope, it is documentary and descriptive. On the other hand, the technique used was direct observation, with its respective instrument, the observation form. The sample comprised 26 students of the initial level 2 "A." On the other hand, the results revealed that both aspects were observed; as for the positive aspects, it is evident that the children have adopted healthy eating habits, reflected in the balanced, varied, and colorful content of their lunch boxes. However, negative aspects have also been identified, such as the lack of implementation of healthy drinks; it has also been observed that some children have difficulties in terms of their eating habits when serving their lunch box, which can impact their general way of eating.